2015
DOI: 10.1128/jcm.03096-14
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Rapid Immunochromatographic Assay for Detection of Middle East Respiratory Syndrome Coronavirus Antigen in Dromedary Camels

Abstract: We present here a rapid immunochromatographic assay for the detection of Middle East respiratory syndrome coronavirus (MERS-CoV) antigen in the nasal swabs of dromedary camels. The assay is based on the detection of MERS-CoV nucleocapsid protein in a short time frame using highly selective monoclonal antibodies at room temperature. The relative sensitivity and specificity of the assay were found to be 93.90% and 100%, respectively, compared to that of the UpE and open reading frame 1A (Orf1A) real-time reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 16 publications
(29 reference statements)
2
42
1
Order By: Relevance
“…Also they reported that the ICA was less sensitive for the detection of MERS-CoV antigen (10 5 TCID50) than was the UpE real-time PCR (10 4 TCID50). The difference between the assay sensitivities might be regarded to the release of subgenomic RNA after the onset of cytopathogenic effect (CPE) in cell culture, including the UpE target fragment, as previously reported [13,14,19]. Also the Rapid MERS-CoV Ag assay cannot detect MERS-CoV loads < 10 4 or Ct value >30.…”
Section: Discussionmentioning
confidence: 91%
“…Also they reported that the ICA was less sensitive for the detection of MERS-CoV antigen (10 5 TCID50) than was the UpE real-time PCR (10 4 TCID50). The difference between the assay sensitivities might be regarded to the release of subgenomic RNA after the onset of cytopathogenic effect (CPE) in cell culture, including the UpE target fragment, as previously reported [13,14,19]. Also the Rapid MERS-CoV Ag assay cannot detect MERS-CoV loads < 10 4 or Ct value >30.…”
Section: Discussionmentioning
confidence: 91%
“…Point-of-care nucleic amplification tests such as RT-loop-mediated isothermal amplification and RT-isothermal recombinase polymerase amplification are suitable for field evaluation, especially in resource-limited areas 250,251 . Similarly, assays that detect abundantly expressed CoV antigens, such as the nucleocapsid protein, can be used for fast and high-throughput laboratory diagnosis without requiring biosafety level 3 containment 252,253 . The rapid availability of complete genome sequences of most human and animal CoVs has minimized the time required for the design of new RT-PCR assays, source identification and molecular surveillance for emerging CoVs 254 .…”
Section: Box 1 | the Complementary Roles Of Novel Rapid Diagnostics Amentioning
confidence: 99%
“…The nonspecific, and sometimes unusual, clinical presentation of MERS in humans, makes early diagnosis difficult in health care facilities. While several highly specific and sensitive molecular and serologic assays exist for diagnosis in animals and humans Corman et al, 2012aCorman et al, , 2012bLu et al, 2014;Perera et al, 2013a;Reusken et al, 2013b;Müller et al, 2015;Song et al, 2015), there was a clear call from representatives from affected countries for the development of a rapid diagnostic test to improve identification and isolation of primary human cases in health care facilities. A full landscape analysis of MERS-CoV diagnostics will be published separately (Van Kerkhove, personal communication).…”
Section: Diagnosticsmentioning
confidence: 99%